Endemic Fish Conservation: Utilization of Cryopreservation Technology with Fructose in Red Bader Fish (Puntius Bramoides) Sperm - Danang Yonarta; Abd Rahem Faqih (Department of Aquaculture, 2023)
Cryopreservation in red bader fish is needed for conservation and development of gamete cell storage. It is a chemical compound that can prevent cell or tissue damage due to freezing. In addition, dimethyl sulfoxide can penetrate cells quickly during equilibration. This research aimed to study reproductive biology and analyze the fructose ability as a extender in the Red Bader fish sperm cryopreservation process. The cryopreservation process was conducted at the Artificial Insemination Center, Singosari. The test fish were obtained from the Freshwater Cultivation Development Center, Umbulan then they were reared for 2 months to get the level of gonad maturity. This study was designed using a completely randomized design (CRD) which consisted of three treatments and three replications. The treatment given was the use of fructose extenders with different percentages i.e., 0.2%, 0.4%, and 0.6%. The results showed that the sperm characteristics of the red bader fish (Puntius bramoides) had a volume of 3.18 mL, a pH value of 7.39, a milky white sperm color, a sperm concentration of 3.5x109 cells/mL, a motility value of 81.67%, and a viability of 85 %. The best type of fructose extender with 0,6% dimethylsulfoxide concentration has a motility value of 38,33% post-cryopservation and 36,67% post-cryopreservation viability. The type of extender affects the sperm quality of angry bader fish during the cryopreservation process, the type of extender obtained was fructose with the best concentration of 0,6% dimethylsulfoxide with the highest motility and viability values.